2016
DOI: 10.1371/journal.pgen.1005835
|View full text |Cite
|
Sign up to set email alerts
|

Type One Protein Phosphatase 1 and Its Regulatory Protein Inhibitor 2 Negatively Regulate ABA Signaling

Abstract: The phytohormone abscisic acid (ABA) regulates plant growth, development and responses to biotic and abiotic stresses. The core ABA signaling pathway consists of three major components: ABA receptor (PYR1/PYLs), type 2C Protein Phosphatase (PP2C) and SNF1-related protein kinase 2 (SnRK2). Nevertheless, the complexity of ABA signaling remains to be explored. To uncover new components of ABA signal transduction pathways, we performed a yeast two-hybrid screen for SnRK2-interacting proteins. We found that Type On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 53 publications
5
72
0
1
Order By: Relevance
“…This mechanism of PP2Cs inhibition is strongly dependent on ABA. It was recently shown that also Type One Protein Phosphatase 1 (TOPP1) regulates the activity of ABA-activated SnRK2s, 20 and it was proposed that regulation of TOPP1 activity and subsequently that of SnRK2s was dependent on PYL11 and ABA. On the other hand, the SnRK2 OST1 interacts with regulatory PP2AA- and PP2AB’-subunits and pp2aa regulatory subunit double mutants show reduced ABA sensitivity in stomatal closure, although pp2a catalytic subunit double mutants show enhanced ABA-dependent SnRK2 activation 21 .…”
mentioning
confidence: 99%
“…This mechanism of PP2Cs inhibition is strongly dependent on ABA. It was recently shown that also Type One Protein Phosphatase 1 (TOPP1) regulates the activity of ABA-activated SnRK2s, 20 and it was proposed that regulation of TOPP1 activity and subsequently that of SnRK2s was dependent on PYL11 and ABA. On the other hand, the SnRK2 OST1 interacts with regulatory PP2AA- and PP2AB’-subunits and pp2aa regulatory subunit double mutants show reduced ABA sensitivity in stomatal closure, although pp2a catalytic subunit double mutants show enhanced ABA-dependent SnRK2 activation 21 .…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that PP1 participates in gibberellin, ABA and auxin signaling as well as photomorphogenesis (Qin et al 2014;Guo et al 2015;Hou et al 2016;Yue et al 2016). Recent work showed that AUN1 (TOPP9) and AUN2 (TOPP8) negatively regulate cell wall integrity maintenance during tip growth (Franck et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…At inhibitor-2). Supporting a negative role of TOPP1 and AtI-2 in ABA signaling, topp1 and atI-2 mutant plants displayed hypersensitivities to ABA and salt treatments [12].…”
Section: Introductionmentioning
confidence: 93%